2002
DOI: 10.1002/art.10511
|View full text |Cite
|
Sign up to set email alerts
|

Effect of urate‐lowering therapy on the velocity of size reduction of tophi in chronic gout

Abstract: Objective. The optimal serum urate levels necessary for elimination of tissue deposits of monosodium urate in patients with chronic gout is controversial. This observational, prospective study evaluates the relationship between serum urate levels during therapy and the velocity of reduction of tophi in patients with chronic tophaceous gout. Method. Sixty-three patients with crystal-confirmed tophaceous gout were treated with allopurinol, benzbromarone, or combined therapy to achieve serum uric acid levels less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
238
0
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 405 publications
(261 citation statements)
references
References 27 publications
6
238
0
9
Order By: Relevance
“…The velocity of crystal dissolution is dependent on the urate concentration 23,24 . Long-term studies have shown the clear clinical benefit of treating patients with urate-lowering therapy (ULT) to reach target serum urate levels, with complete suppression of flares, regression of tophi and improvement in quality of life over time 21,[25][26][27][28][29][30] . Bone erosions due to tophaceous gout also have been shown to heal after expedited eradication of tissue MSU crystal deposits by use of pegloticase therapy 31 .…”
Section: Rationale For the G-can Positionmentioning
confidence: 99%
“…The velocity of crystal dissolution is dependent on the urate concentration 23,24 . Long-term studies have shown the clear clinical benefit of treating patients with urate-lowering therapy (ULT) to reach target serum urate levels, with complete suppression of flares, regression of tophi and improvement in quality of life over time 21,[25][26][27][28][29][30] . Bone erosions due to tophaceous gout also have been shown to heal after expedited eradication of tissue MSU crystal deposits by use of pegloticase therapy 31 .…”
Section: Rationale For the G-can Positionmentioning
confidence: 99%
“…It is shown that recurrent gouty attacks are better prevented [12,13] and that tophi dissolve more quickly [14] in the presence of sUr levels ≤0.30 mmol/l, compared with levels 0.30-0.36 mmol/l. Thus, we aimed the sUr treatment goal for gout patients at ≤0.30 mmol/l.…”
Section: Introductionmentioning
confidence: 99%
“…(9,10) Tophus size was also demonstrated to reduce more rapidly in patients with lower SUA levels. (11) …”
Section: Introductionmentioning
confidence: 99%